Peran Pembimbing Rohani Islam Dalam Menumbuhkan Rasa Optimis Terhadap Pasien Keguguran di Rumah Sakit Roemani Muhammadiyah Semarang - Kusumawati, Fani Suci; Septianti, Zona Dwi; Rosyida, Ratna Nirmala; Safitri, Diah Kurnia; Wardani, Bunga Suci; Alghifahmy, Ayu Faiza (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2024)
This article discusses the role of Islamic spiritual guides in fostering optimism among patients who have experienced miscarriage at Roemani Muhammadiyah Hospital in Semarang. Miscarriage is a highly emotional experience that often leads to deep feelings of loss for patients. In this context, spiritual guides serve as a source of spiritual support, helping patients cope with sadness and uncertainty. Through spiritual approaches and effective communication, spiritual guides can assist patients in processing their experiences in a more positive manner. Additionally, support from family members is also a crucial factor in rebuilding the patients' optimism. The synergy between family support and spiritual guidance is vital in helping patients navigate the healing process holistically. This research shows that appropriate emotional and spiritual support can mitigate the psychological impact of miscarriage and expedite the healing process. Keywords: spiritual guide, miscarriage, optimism, family support, Roemani Muhammadiyah Hospital Semarang.